Bacillus sp. UPM-AAG1 for The Bioremediation of Ammonia in Aquaculture Wastewater (Bioremediation Science and Technology Research (e-ISSN 2289-5892), 2019)
The widespread activity of the aquaculture industry has led to environmental pollution resulting from the uncontrollable production of ammonia from aquaculture activities. The presence of ammonia in the environment is a major threat due to its toxicity that can bring harm to organism especially aquatic organisms. Bioremediation is an efficient technique for the remedy of ammonia pollution as it provides complete assimilation of the ammonia.  In this work, a bacterial isolate identified as Bacillus strain UPM-AAG1 shows the best performance out of the four isolates screened for remediating ammonia.  The characterization of Bacillus strain UPM-AAG1 was conducted to identify the optimum conditions for ammonia utilization by Bacillus strain UPM-AAG1. The optimum pH for ammonia remediation by Bacillus strain UPM-AAG1 was determined to be acidic at pH 6.0. While the optimum condition for ammonia concentration was determined to be at 10 mg/mL. For the optimum temperature for ammonia remediation by Bacillus strain UPM-AAG1 was determined to be at 30 oC.
Keywords: Bacillus sp.; ammonia; optimization; bioremediation; aquaculture